Zebrafish as a Vertebrate Model for Studying Nodavirus Infections - Lama, Raquel; Pereiro, Patricia; Figueras, Antonio; Novoa, Beatriz (Frontiers in Immunology, 2022)
Nervous necrosis virus (NNV) is a neurotropic pathogenic virus affecting a multitude of marine and freshwater fish species that has a high economic impact on aquaculture farms worldwide. Therefore, the development of new tools and strategies aimed at reducing the mortality caused by this virus is a pivotal need. Although zebrafish is not a natural host for NNV, the numerous experimental advantages of this species make zebrafish an attractive model for studying different aspects of the disease caused by NNV, viral encephalopathy and retinopathy (VER). In this work, we established the best way and age to infect zebrafish larvae with NNV, obtaining significant mortalities in 3-day-postfertilization larvae when the virus was inoculated directly into the brain or by intramuscular microinjection. As occurs in naturally susceptible fish species, we confirmed that after intramuscular injection the virus was able to migrate to the central nervous system (CNS). As expected, due to the severe damage that this virus causes to the CNS, alterations in the swimming behaviour of the zebrafish larvae were also observed. Taking advantage of the existence of transgenic fluorescent zebrafish lines, we were able to track the migration of different innate immune cells, mainly neutrophils, to the site of infection with NNV via the brain. However, we did not observe colocalization between the viral particles and neutrophils. RNA-Seq analysis of NNV-infected and uninfected larvae at 1, 3 and 5 days postinfection (dpi) revealed a powerful modulation of the antiviral immune response, especially at 5 dpi. We found that this response was dominated by, though not restricted to, the type I interferon system, the major defence mechanism in the innate immune response against viral pathogens. Therefore, as zebrafish larvae are able to develop the main characteristic of NNV infection and respond with an efficient immune arsenal, we confirmed the suitability of zebrafish larvae for modelling VER disease and studying different aspects of NNV pathogenesis, immune response and screening of antiviral drugs.